Exploration of Student Learning Experiences in Using the Drill and Practice Method with a Gamification Approach in Learning Aqidah and Akhlak at MTs Darul Ulum - Layla Nur Zakia; Dedi Setiawan; Adi Wijaya (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by the problem of low learning motivation among Generation Z students who tend to be bored with traditional memorization methods in learning Akidah Akhlak. Based on this, this study aims to explore in depth the learning experiences of students at MTs Darul Ulum in using the Drill and Practice method with a Gamification approach. This type of research is field research with a qualitative-phenomenological approach. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model. The results show that the use of gamification elements such as points, leaderboards, and instant challenges effectively changed students' perceptions from the burden of memorization to a fun, competitive challenge. The main supporting factors in this implementation are the availability of supporting infrastructure, teacher readiness in managing interactive media, and high student internal motivation to gain recognition of competence. However, the study also identified an inhibiting factor in the form of time pressure that triggers anxiety in a small number of students with slow learning speeds, thus risking lowering their self-confidence. Phenomenologically, this experience is interpreted as an interactive process that increases self-efficacy, but still requires the role of the teacher as a mentor to maintain a balance between extrinsic motivation and instilling the value of sincerity so that the essence of religious learning is maintained.